Urgensi Akhlak Seorang Pendidik (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2018)
The character of an educator is shaped by his/her faith and is manifested in numerous forms of attitude. Good character is not shaped merely by the lesson, instruction, or prohibition. For the soul to take its honor cannot be provided only by teacher’s saying to do a thing or not to do other things. Instilling good morals requires a life time education. Education will not succeed without providing a real example of good character. The character of the educators is the most effective form of this example, especially to lead individuals to have good character, good faith, and piety toward Allah the Almighty. The noble characteris embodied in attitudes that are based on religious teaching, social norms, and are not against the local wisdoms. It is universal in nature and accepted by anyone and anywhere. This must have character for the educators is viewed important either from the aspects of faith and worship or in the aspects of human relation or character. Teachers as the educators are expected to give guidance and advice. Accordingly, they have to apply it themselves first hand because they are the role model to be followed anywhere they are. Good character is in the very top position in human life. The importance of good character is not only matter in individual life. It is also very necessary in family and community life. In fact, it is a matter that shapes a nation.